PFAPA Syndrome: Diagnosis and Treatment in Primary Health Care - Bueno, Laniel Aparecido (2019)
Objective: To present information about the diagnosis and treatment of PFAPA syndrome in Primary Health Care. Methods: Systematic review of literature based on the PRISMA recommendation and carried out in the Scielo, Lilacs, Medline, IBECS and PubMed databases, including studies published from 2004 to 2018, in addition to consulting other PFAPA syndrome specific documents. Results: After search and selection, 31 articles were included. Assessment and Diagnosis: PFAPA syndrome affects mainly children and is characterized by periodic fever accompanied by pharyngitis, aphthous stomatitis and/or cervical adenitis. Its diagnosis is clinical and by exclusion, based on established criteria. Recommendations: The episodes usually respond to prednisone and, in varying levels, cimetidine and colchicine. Refractory cases and accompanied by tonsillar hypertrophy are candidates for tonsillectomy, and should be referred to otorhinolaryngological evaluation.